2018
DOI: 10.1111/eos.12406
|View full text |Cite
|
Sign up to set email alerts
|

Factors predictive of the onset and duration of action of local anesthesia in mandibular third‐molar surgery: a prospective study

Abstract: The aim of this study was to assess the influence of patients' and surgical variables on the onset and duration of action of local anesthesia (LA) in mandibular third-molar (M3) surgery. Patients scheduled for mandibular M3 surgery were considered for inclusion in this prospective cohort study. Patients' and surgical variables were recorded. Two per cent (2%) lidocaine with 1:100,000 epinephrine was used to block the nerves for extraction of mandibular M3. Then, the onset of action and duration of LA were moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Smokers had slightly longer anesthesia duration in comparison to non-smokers in all three groups, however statistical signi cance was noted only in Group 3. This nding to some extent corroborated with another study where smokers also had increased mean values of local block anesthesia duration, although after lidocaine with epinephrine application [35]. The results of our study referring to Group 1 and 3 con rmed earlier observations where soft tissue anesthesia duration was not related to patients' sex [36].…”
Section: Discussionsupporting
confidence: 92%
“…Smokers had slightly longer anesthesia duration in comparison to non-smokers in all three groups, however statistical signi cance was noted only in Group 3. This nding to some extent corroborated with another study where smokers also had increased mean values of local block anesthesia duration, although after lidocaine with epinephrine application [35]. The results of our study referring to Group 1 and 3 con rmed earlier observations where soft tissue anesthesia duration was not related to patients' sex [36].…”
Section: Discussionsupporting
confidence: 92%
“…[28][29][30] This is because a higher volume of the anesthetic agent may yield a higher concentration of the anesthetic agent in the pterygomandibular space. 29 Moreover, Al-Shayyab et al 35 found that many factors could affect the onset time and duration of action of local anesthesia, such as age, gender, and smoking status. However, the studies included in this review did not present enough information for analysis, so there is still some unexplained heterogeneity.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…In this line, authors agree that there could be confounding factors that we did not retrieved from the selected articles, that could clarify the named "unexplained heterogeneity." However, the article by Al-Shayyab and Baqain, 4 which the authors cited in their letter, curiously admits that there is little information available about the influence of variables, such as sex, on the efficacy of local anesthetics.…”
Section: Authors' Responsementioning
confidence: 99%